Small substrate, big surprise: fold, function and phylogeny of dihydroxyacetone kinases. - Erni, B; Siebold, C; Christen, S; Srinivas, A; Oberholzer, A; Baumann, U (2006)
Dihydroxyacetone (Dha) kinases are a family of sequence-conserved enzymes which utilize either ATP (in animals, plants and eubacteria) or phosphoenolpyruvate (PEP, in eubacteria) as their source of high-energy phosphate. The kinases consist of two domains/subunits: DhaK, which binds Dha covalently in hemiaminal linkage to the Nepsilon2 of a histidine, and DhaL, an eight-helix barrel that contains the nucleotide-binding site. The PEP-dependent kinases comprise a third subunit, DhaM, which rephosphorylates in situ the firmly bound ADP cofactor. DhaM serves as the shuttle for the transfer of phosphate from the bacterial PEP: carbohydrate phosphotransferase system (PTS) to the Dha kinase. The DhaL and DhaK subunits of the PEP-dependent Escherichia coli kinase act as coactivator and corepressor of DhaR, a transcription factor from the AAA(+) family of enhancerbinding proteins. In Gram-positive bacteria genes for homologs of DhaK and DhaL occur in operons for putative transcription factors of the TetR and DeoR families. Proteins with the Dha kinase fold can be classified into three families according to phylogeny and function: Dha kinases, DhaK and DhaL homologs (paralogs) associated with putative transcription regulators of the TetR and DeoR families, and proteins with a circularly permuted domain order that belong to the DegV family.